A Perspectiveon Predicting Currency Crises - Flood, Robert; Marion, Nancy; Yepez, Juan. (Washington, D.C. : International Monetary Fund, 2010)
Currency crises are difficult to predict. It could be that we are choosing the wrong variables or using the wrong models or adopting measurement techniques not up to the task. We set up a Monte Carlo experiment designed to evaluate the measurement techniques. In our study, the methods are given the right fundamentals and the right models and are evaluated on how closely the estimated predictions match the objectively correct predictions. We find that all methods do reasonably well when fundamentals are explosive and all do badly when fundamentals are merely highly volatile.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet